2003
DOI: 10.1080/13617670305422
|View full text |Cite
|
Sign up to set email alerts
|

'Cleanliness is Next to Godliness': A further look

Christopher Alan Lewis

Abstract: reviews the empirical relationship between aspects of religiosity (attitude, practice, and orientation) and measures of obsessionality (personality traits and obsessional symptoms) among non-clinical samples based on studies published between 1981 -96. Lewis (1998 draws three conclusions: (1) religious attitude is associated with obsessional personality traits, but not with obsessional symptoms; (2) religious practice is associated with obsessional personality traits, but not with obsessional symptoms; and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…From such research a number of conclusions can be drawn. First, the examination of the Freudian theory (1927/1961) that religion is an obsessional neurosis demonstrates that higher obsessional personality trait scores, rather than obsessional symptoms scores, are associated with greater religiosity (for a review see Lewis, 1998Lewis, , 2003. Second, the location of religiosity within Eysenck's Three-dimensional Model of Personality (e.g., Eysenck & Eysenck, 1985), demonstrates that lower Psychoticism scores (i.e., tendermindedness), rather than extraversion or neuroticism or Lie Scale scores, are associated with greater religiosity (for a review see Francis, 1992;Lewis & Francis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From such research a number of conclusions can be drawn. First, the examination of the Freudian theory (1927/1961) that religion is an obsessional neurosis demonstrates that higher obsessional personality trait scores, rather than obsessional symptoms scores, are associated with greater religiosity (for a review see Lewis, 1998Lewis, , 2003. Second, the location of religiosity within Eysenck's Three-dimensional Model of Personality (e.g., Eysenck & Eysenck, 1985), demonstrates that lower Psychoticism scores (i.e., tendermindedness), rather than extraversion or neuroticism or Lie Scale scores, are associated with greater religiosity (for a review see Francis, 1992;Lewis & Francis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this special issue, co-edited by Lewis and Loewenthal who have both published widely in the area of religion and obsessional neurosis (e.g., Al-Solaim & Loewenthal, 2011;Lewis, 1994Lewis, , 1996Lewis, , 1998Lewis, , 2001Lewis, , 2003Lewis & Joseph, 1994a, 1994bLewis & Maltby, 1992, 1994, 1995Loewenthal, 1995Loewenthal, , 2006Loewenthal, , 2009Yossifova & Loewenthal, 1999), was to provide a forum for the collection of pertinent papers, and thereby providing both an overview of the current state of the literature, as well as providing a possible stimulation for future research.…”
Section: Religion and Obsessionality: Obsessive Actions And Religiousmentioning
confidence: 99%
“…The relation between religiosity and obsessional illness has been discussed by a number of authors. A review by Lewis (1998) suggested that religiosity is associated with obsessional traits but not with obsessional neurosis. Similarly, Greenberg & Witztum (2001) pointed out that a review of the prevalence of obsessive-compulsive disorder in a variety of cultural backgrounds does not implicate religious background as a causative factor in this disorder.…”
Section: Religious Behaviour or Obsessional Illness?mentioning
confidence: 99%